CBCT analysis of bone density in bicortical defects after augmentation with alloplastic and xenogeneic bone substitutes – A study on domestic pigs - Djordjević, Filip; Mihailović, Branko; Mladenović, Raša; Dubovina, Dejan; Kostić, Mirjana; Stanišić, Jelena; Vlahović, Zoran (Vojnosanitetski pregled, 2021)
Background/Aim. A significant benefit in bicortical defects healing can be achieved by guided tissue and guided bone regeneration. The aim of this study was a cone-beam computed tomography (CBCT) radiographic bone density analysis of bicortical defects healing when treated with guided bone regeneration and two bone substitutes – bovine xenograft and alloplastic bone substitute. Methods. The research was performed on domestic pigs in two phases. In the first phase, extraction of all teeth in the intercanine sector was performed in the lower jaw and postextraction wounds were sutured. In the second phase, after the period required for healing, bicortical defects were formed – following the elevation of mucoperiosteal flaps from the vestibular and lingual side in the area of the previously extracted teeth, surgical removal of the cambium layer of periosteum was performed in the area of future defects with sharp surgical scissors and curette. Two defects, 10 mm in diameter, on the left and right side of the medial line were formed and filled with alloplastic bone substitute on the left and xenograft on the right side afterward. After augmentation, the defects were covered by a collagen resorptive membrane on both sides, and the flap was repositioned and sutured. After 12 weeks, experimental animals were sacrificed. The surrounding native bone was used as a control. Results. Analysis of bone tissue density showed a statistically significant difference between the examined bone substitutes (p < 0.01), with a better effect achieved by the use of alloplastic bone substitute. After applying Bonferroni correction, the difference was still statistically significant. Conclusion. Both bone substitutes used in the study showed good osteoconductive properties in the treatment of bicortical defects. Bone tissue density in defects filled with alloplastic bone graft was statistically significantly higher than that in the defects filled with xenograft.